Malay Version of the ATS-DLD-78A Questionnaire for Detecting Respiratory Symptoms in Welders: Translation and Cross-Cultural Validation. - Zainal Bakri, Siti Farhana; Hariri, Azian; MarzIsmail, Marzuki (2023)
The role of the questionnaire in epidemiological and public health studies has received increased attention across a number of disciplines. In a respiratory study, the progress of research in cross-cultural settings is reflected in the systematic application of clinical and research data collection that is quantifiable and reliable. However, one of the main obstacles is language. To date, there has been no reported evidence pertaining to the translation of the respiratory symptoms questionnaire into Malay, the national and most widely used language in Malaysia. Therefore, this paper presents a translation method for ATS-DLD-78A, the respiratory symptoms questionnaire, into the Malay language using a forward-backwards translation approach. This pilot study was conducted to validate a questionnaire on respiratory symptoms in a Malaysian welder population. A total of 28 welders were enrolled in this pilot study. The internal reliability and validity of the questionnaire were assessed. The Cronbach's alpha was 0.812, which is high and considered good. All other correlations using Pearson are significant, indicating that the concepts measured by the items and the translated questionnaire were valid and clearly understood by the participants. This will greatly contribute to the field of a respiratory epidemiological study in Malaysia.